2008
DOI: 10.1108/13581980810918413
|View full text |Cite
|
Sign up to set email alerts
|

The impact of corporate fairness on the bank‐SME relationship

Abstract: Purpose -The United Kingdom Financial Services Authority's treating customers fairly initiative has drawn attention to a current trend that involves regulators using regulatory principles to enhance the relationship between financial institutions and customers. The term corporate fairness is introduced to facilitate the understanding of the construction of fairness. The purpose of this study is to investigate corporate fairness as a means of achieving customer satisfaction. Design/methodology/approach -This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 60 publications
2
5
0
Order By: Relevance
“…These findings are in line with the finding of Vegholm and Silver (2008) and Llewellyn (2005), who argues that it is important for financial institutions to set guidelines for individual bankers on how to act fairly, and to develop appropriate training and reward mechanisms. The finding is also consistent with those of Seal (1998), who argues that a trustworthy organization starts by building confidence into its internal processes, through training and educating its own employees.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…These findings are in line with the finding of Vegholm and Silver (2008) and Llewellyn (2005), who argues that it is important for financial institutions to set guidelines for individual bankers on how to act fairly, and to develop appropriate training and reward mechanisms. The finding is also consistent with those of Seal (1998), who argues that a trustworthy organization starts by building confidence into its internal processes, through training and educating its own employees.…”
Section: Discussionsupporting
confidence: 79%
“…Building upon Llewellyn's (2005) proposed model, the present study has shown that it is indeed in the best interest of financial institutions to strive for corporate fairness. Although this study finding partially replicates previous research (e.g., Hansen & Riggle, 2009;Chen & Mau, 2009;Roma´n, 2003;Vegholm & Silver, 2008;Roma´n & Munuera, 2005;Llewellyn, 2005;Lagace et al, 1991;Román & Ruiz 2005), but the other one represent new contributions to the research body. However, it is an attempt to occupy the gab in interrelationships that were uncovered between ethical sales behavior, relationship quality (customer trust and customer commitment) and customer loyalty.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The reasons advanced for this include the programmes being irrelevant or the SMMEs not being aware of the existence of such programmes. Vegholm and Silver (2008) note that most traders favour networking with financial institution managers who are most likely to assist them during times of trouble instead of the government programmes.…”
Section: Support For Cross-border Tradementioning
confidence: 99%
“…Temtime, Chinyoka and Shenda (2004) point out that banks have been criticised for being insensitive to the SMME sector. They are accused of demanding strict collateral security and charging punitive interests rates (Vegholm & Silver 2008). …”
Section: Assistance In Cross-border Tradingmentioning
confidence: 99%